Correlation of degree and pattern of contrast enhancement on Magnetic Resonance Imaging with histopathological grade of intracranial astrocytoma - Mohammad Nuruzzaman Khan; Sabrina Shafiq; Syed Shahreor Razzaque; Sk Sader Hossain (Journal of Shaheed Suhrawardy Medical College, 2024)
Background/Objective: Astrocytomas, a type of glioma, require accurate grading to guide treatment. This study evaluates the correlation between MRI contrast enhancement and histopathological grades of astrocytomas. Methods: A cross-sectional study of 37 patients with biopsy-confirmed astrocytomas was conducted. Non-probability or purposive sampling was carried out. MRI scans assessed contrast enhancement characteristics, and tumors were classified radiologically and histopathologically. Results: The age range of the patients was 11 to 74 years and mean age was 40.25±16.04 years. The male to female ratio was 4:1. Headache was the most common presenting symptoms (95%). Most of the tumors were located at the cerebral hemispheres (78%). None or slight contrast enhancement was found in 17 (46%) and the pattern of contrast enhancement was heterogeneous in 24 (65%) patients. Maximum 20 (54%) patients had high grade astrocytoma. In the present study, 85% high grade astrocytoma showed moderate to marked whereas 82.4% low grade astrocytoma showed none or slight contrast enhancement. Sensitivity & specificity of contrast enhanced MRI was 82.4% and 85% respectively. The overall accuracy was 83.78%. Conclusion: MRI is a reliable non-invasive tool for grading astrocytomas, with strong correlation between contrast enhancement and tumor grade, supporting its use in clinical decision-making. J Shaheed Suhrawardy Med Coll 2023; 15(1): 13-19